(3GdHQgGf aj CUhd Gdabgs - (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdLhjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3GYde Efg Mb Ydi cd ef jMGhd GdNhV ai af ef afhf GdYde s
(3BNQgG (B:s
(3ai GdaYd GdeWdb aEf JbjO HbQjfI OGdI Ydi s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B184s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs